Data Sharing, Year 1 — Access to Data from Industry-Sponsored Clinical Trials - Strom, Brian L; Buyse, Marc; Hughes, John; Knoppers, Bartha M (The New England journal of medicine, 2014)
Since May 2013, researchers have been able to request access to deidentified patient-level data from GlaxoSmithKline–sponsored clinical trials, subject to oversight by an independent review panel. The initiative has been a productive first step in transparency. There has been considerable interest of late in increasing the transparency of clinical trials, including increasing access to the raw data from trials sponsored by the pharmaceutical industry. 1 Since May 2013, investigators have been able to request access to deidentified patient-level data from clinical trials sponsored by GlaxoSmithKline, 2 subject to review and oversight by an independent review panel (https://clinicalstudydatarequest.com/Default.aspx). As the members of this panel, we now have more than 12 months of experience with this initiative — and can report that it has been a productive and successful first step. The system was launched on May 7, 2013, and . . .